PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PENDAPATAN PETANI GAMBIR DI KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA KOTA - Ana Tasya Rahima; Mega Amelia Putri; Arnayulis Arnayulis (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The aim of this study is to examine the effects of land area, labor, production costs, production quantities, and prices simultaneously and partially on the income of gambier farmers in Pangkalan Koto Baru District. The research method uses multiple linear regression. Determination of the purposive sampling amounted to 30 respondents. The results showed that simultaneously the variables of land area, labor, production costs, production quantities and prices had a significant effect on income. Partially shows that the variables of labor, production costs and the amount of production have a significant effect on income while the variables of land area and price have no significant effect on the income of gambier farmers in Pangkalan Koto Baru District. Based on the coefficient of determination of 82.3%, the income of gambier farmers in Pangkalan Koto Baru District is dependent on all independent variables. and the remaining 17.7% from other variables.